2017
DOI: 10.1016/j.snb.2016.12.010
|View full text |Cite
|
Sign up to set email alerts
|

A G-quadruplex aptamer based impedimetric sensor for free lysine and arginine

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that: • a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Disposable gold screen printed electrodes are already available on the market as an alternative to the conventional electrodes. More recently, gold-sputtered microelectrodes have become commercially available as an attractive platform for the development of miniaturized biosensors through covalent attachment of biomolecules to the gold surface via thiols [1][2][3][4][5] . These microelectrodes are made up of gold, sputtered with a thickness of 10-500 nm on a glass substrate directly or through an intermediate layer of chromium for better adhesion 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Disposable gold screen printed electrodes are already available on the market as an alternative to the conventional electrodes. More recently, gold-sputtered microelectrodes have become commercially available as an attractive platform for the development of miniaturized biosensors through covalent attachment of biomolecules to the gold surface via thiols [1][2][3][4][5] . These microelectrodes are made up of gold, sputtered with a thickness of 10-500 nm on a glass substrate directly or through an intermediate layer of chromium for better adhesion 1 .…”
Section: Introductionmentioning
confidence: 99%
“…However, depending on the type of aptamer its binding affinity is subject to change as a function of conditions. In our case the presence of K + or Mg 2+ may interfere (Carter and Kataky, 2017;Fiegland et al, 2012;Noireaux, 2012, 2010).…”
Section: Introductionmentioning
confidence: 65%
“…Furthermore antibodies are sensitive to chemical conditions (Jayasena, 1999;Song et al, 2008). A lysine aptamer can bind very specifically against lysine (Carter and Kataky, 2017;Fiegland et al, 2012;Sudarsan et al, 2003). However, depending on the type of aptamer its binding affinity is subject to change as a function of conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that G-quadruplex DNA or RNA could fold into a stable structure and bind to various targets in vivo or in vitro [ 71 , 72 ]. Some aptamers with G-quadruplex motifs were also reported to bind to small molecules with high affinity, such as GTX [ 58 ], aflatoxin [ 73 ], lysine, arginine [ 74 ], etc.…”
Section: Resultsmentioning
confidence: 99%